MOTIVATION AND SATISFACTION IN CONTEXT OF JOB TRAINING IN TOURIST ORGANIZATIONS - Amaral, Rui (2017)
This research aims to determine the dimensions of motivation and satisfaction, acquired, through the perception in context of job training, by future technicians (students) in the hospitality and tourism industry, particularly by technical courses in the hotel and restaurant sector. The methodology comprises three distinct stages. First were recovered instruments (questionnaires), already validated by other authors of motivation and satisfaction, which had the intention to replicate studies conducted in other scientific knowledge fields, such as tourism. Those instruments were recovered from the reviewed literature conducted about other themes. On second place the measuring instruments were submitted to a pre-test, or rather, were subject of a pioneer study, in order to verify other assumptions such as semantic errors or see if there was the possibility of some prepared questions to be consider invalidated by poor formulation or interpretation. Finally, were applied in three educational institutions who agreed to cooperate on the research, with the reservation that the interviewed needed a mandatory pre-requirement that consisted in conducting a minimum training in work context (TWC). Then, proceed the statistical analysis to support all the empirical part. The results show that, in general, motivation and satisfaction were present during the period of training in work context. To some people it meant a very important period of personal and professional life, concerning the interactions, emotions and involvement with touristic organizations but also the personal and social relationships.